Impact of corporate governance and institutional context on multilatinas’ reporting quality (2022)
ABSTRACT: Purpose – This study aims to identify the impacts of corporate governance (CG) and institutional context on multilatinas’ corporate reporting quality (CRQ). CG and institutional context facilitate the reduction of agency problems and the existence of accountability processes that minimize information asymmetries. Design/methodology/approach – A panel data model was developed from a sample of 77 multilatinas studied during the 2014–2020 period. Different estimations were carried out through the panel data model to identify the impact of CG and institutional context on CRQ. Findings – It is evidenced that appropriate CG structure has a positive impact on multilatinas’ CRQ. In addition, each country’s regulatory quality is confirmed to have a positive effect on firms to produce higher-quality reports. Practical implications – This research provides empirical support to what is put forward by agency and stakeholder theory regarding the role that CG and institutional context play in reducing information asymmetries and improving accountability processes to all stakeholders in the Latin American context. Originality/value – This study contributes original results to the existing literature. Unlike previous works, the present research analyzed multilatinas facing social and political contexts that differ from those of multinationals from developed countries. Different ways of reporting were also covered, going beyond traditional ways of evaluating CRQ – which generally take the sustainability report as a basis.